Analysis and Implementation of Pulse-Width Modulated DC-DC Converter for Electric Vehicles with Improved Efficiency - Venkata Ravi Kishore Kanamarlapudi (2017)
This paper presents new gating techniques to improve the efficiency of zero-voltage zero-current switching (ZVZCS) full-bridge DC-DC converter for battery charging in electric vehicles. The converter is assisted by a passive auxiliary circuit to extend the zero voltage switching range. The uncontrolled auxiliary circuit current increases the conduction losses of the converter when gated with conventional phase-shift modulation (PSM) technique. The controlled auxiliary circuit current with the proposed pulse-width modulation (PWM) gating techniques increases the efficiency of the converter especially at light-load conditions compared to PSM. In this paper, the steady-state analysis of the converter auxiliary circuit with the PWM gating techniques is presented. A comparative loss analysis with PWM and PSM gating techniques is also given. A 1.2-kW, 100-kHz converter is implemented on ORCAD-Pspice and the simulation results are presented to validate the improvement in efficiency of the converter with the proposed PWM gating techniques.